Pentingnya Penggunaan Media Visual dalam Meningkatkan Pemahaman Nilai Agama pada Anak Usia Dini - Sidiq, Nurul Jamiah; Islami, Andi Nur Maharani; Rusliana, Faradillah; Manga, Delvhina; Hasmawaty (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Understanding religious values in early childhood is a fundamental foundation for shaping character and behavior in accordance with religious teachings. This study analyzes the effectiveness of using visual media, such as pictures and posters, in enhancing the comprehension of religious values at Raudhatul Athfal Arrahman Tinggito Kindergarten. Using a descriptive qualitative approach, the research involved observations of the learning process for children aged 5-6 years, interviews with teachers and parents, and documentation of learning activities. The results indicate that visual media is highly effective in helping children grasp abstract religious concepts, reducing cognitive load, and increasing interest and participation in learning. Pictures and posters not only facilitate the understanding of worship practices, such as prayer and ablution, but also connect physical actions with spiritual meanings. This study contributes to the development of interactive and effective religious learning methods in Early Childhood Education (ECE) and highlights the importance of collaboration between teachers and parents in supporting children's learning.